Pulp tissue vacuolization and necrosis after direct pulp capping with calcium hydroxide and transforming growth factor-β1 - Sri Kunarti (Dental Journal (Majalah Kedokteran Gigi), 2008)
Mechanical pulp exposure by a rotary cutting instrument or a hand-cutting instrument often happens in deep caries. Application of protective dressing can protect the pulp from additional injury by facilitating healing and repair. Pulp capping has been suggested as one treatment of choice after pulp exposure to maintain pulp vitality. TGF-β1 is growth factor that has important rule in wound healing. The application of Ca(OH)2 and exogenous TGF-β1 as direct pulp capping tr4eatment must be experimented in-vivo to see the vacuolization and necrosis in 7, 14, and 21 days after application. This research was done in vivo experiment from orthodontic patients indicated for premolar extraction, between ages 10–15 years. A class V cavity preparation was created in the buccal aspect 1 mm above gingival margin until pulp exposure. Cavity was irrigated slowly with saline solution and dried with a sterile small cotton pellet. Group 1 calcium hydroxide was applied as manufacture procedure. Group 2, the sterile absorbable collagen membrane used, as inert carrier of TGF-β1 was soaked with 5 ml. All groups were covered by a Teflon pledge to separate pulp capping agent from glass ionomer cement restoration. Teeth extracted in 7, 14 and 21 days after treatment. All samples were hystopathologically examined. There were significant difference of TGF-β1 (p < 0.05) in the vacuolization day 14th and 21th compared with 7th. there were not significant difference in necrosis for all variables. Vacuolization and necrosis decreased in the application of TGF-β1.